EVALUATION OF THE PERFORMANCE TRADING COMPANIES IN SERBIA BASED ON THE FF-WASPAS AND WASPAS METHODS - Lukić, Radojko (The European Journal of Applied Economics, 2023)
Recently, when analyzing the performance of trading companies, various multi-criteria decision-making methods are increasingly used individually or integrated. This way, because several criteria are simultaneously used integrally, a realistic idea of the achieved performance is obtained in comparison to classical methods. Based on that, this paper analyzes the performance of trading companies in Serbia based on the FF-WASPAS and WASPAS methods. According to the FF-WASPAS method, the top five trading companies in Serbia in terms of performance are in order: DELHAIZE SERBIA DOO BELGRADE, LIDL SERBIA KD NOVA PAZOVA, NELT CO. DOO BELGRADE, MERCATOR-S DOO NOVI SAD AND MOL SERBIA DOO BELGRADE. The worst position was taken by the trading company PHOENIX PHARMA DOO BELGRADE. According to the WASPAS method, the top five trading companies in terms of performance are in order: DELHAIZE SERBIA DOO BELGRADE, LIDL SERBIA KD NOVA PAZOVA, MERCATOR-S DOO NOVI SAD, NELT CO. DOO BELGRADE AND MOL SERBIA DOO BELGRADE. The trading company KNEZ PETROL DOO ZEMUN took the worst position. Recently , under the positive influence of numerous macro and micro factors (favorable economic climate, efficient management of human resources, assets, capital, sales and profit, digitization of the entire business, etc.), the performance of trading companies in Serbia has improved